Tax and government in the twenty-first century / Miranda Stewart, University of Melbourne. - Stewart, Miranda, 1968- (Law in context., 2022)
With an accessible style and clear structure, Miranda Stewart explains how taxation finances government in the twenty-first century, exploring tax law in its historical, economic, and social context. Today, democratic tax states face an array of challenges, including the changing nature of work, the digitalisation and globalisation of the economy, and rebuilding after the fiscal crisis of the COVID-19 pandemic. Stewart demonstrates the centrality of taxation for government budgets and explains key tax principles of equity, efficiency and administration. Presenting examples from a wide range of jurisdictions and international developments, Stewart shows how tax policy and law operate in our everyday lives, ranging from family and working life to taxing multinational enterprises in the global digital economy. Employing an interdisciplinary approach to the history and future of taxation law and policy, this is a valuable resource for legal scholars, practitioners and policy makers.